2010
DOI: 10.1055/s-0039-1697834
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Compliance with Hand Hygiene by Dental Healthcare Personnel (DHCP) within a Dentistry Healthcare First Aid Facility

Abstract: Objectives:To evaluate the compliance with the opportunities of hand hygiene by dentistry school healthcare professionals, as well as the higher choice products.Methods:Through direct observation, the oral healthcare team-professors, oral and maxillofacial surgery residents, graduation students-for daily care were monitored: before performing the first treatment of the shift, after snacks and meals, and after going to the bathroom (initial opportunities) as well as between patients’ care, and after ending the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…HBV has demonstrated the ability to survive and remain infectious in dried blood on environmental surfaces for at least 1 week and probably longer [ 1 ], [ 20 ]. Therefore, dental procedures can introduce oral pathogens into the bloodstream or lymphatic system via direct hematogenous spread or aspiration, thereby causing various medical conditions including bacteremia, pneumonia, or infective endocarditis [ 21 ], [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV has demonstrated the ability to survive and remain infectious in dried blood on environmental surfaces for at least 1 week and probably longer [ 1 ], [ 20 ]. Therefore, dental procedures can introduce oral pathogens into the bloodstream or lymphatic system via direct hematogenous spread or aspiration, thereby causing various medical conditions including bacteremia, pneumonia, or infective endocarditis [ 21 ], [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider that the pathways of contamination are bi-directional: Both patients and dental health care personnel (DHCP) may be exposed to a number of pathogens through exposure to blood and saliva [ 1 ]. In addition, the hands of DHCP may serve as a reservoir for pathogens [ 2 ], including multi-resistant strains [ 3 ]. Infection control forms an important part of practice for all health care professions and remains one of the most cost-beneficial medical interventions available [ 4 ], [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings de-Amorim-Finzi et al (2010) reported only 45% compliance of hand hygiene among the graduation students. [15] The low compliance with regular hand washing necessitates stricter measures to remind the students of the importance of hand washing. Hand washing signs can be placed near each basin in dental clinics since hand washing is a significant element in infection control.…”
Section: Vaccination Statusmentioning
confidence: 99%
“…Indeed, a recent review (WHO, 2009) reported an average compliance of 38.7% with a baseline ranging from 5% to 89%. These results are inferior than many studies conducted for dental healthcare workers in countries such as Africa (25% before glowing and 47% after),[ 7 8 ] Italy (55.5%),[ 13 ] Canada (76%),[ 14 ] USA (75%)[ 22 ], Khartoum state (44%),[ 15 ] United Kingdom (26–63%). [ 23 ] Moreover, it is important to distinguish between studies undertaken in teaching and nonteaching centers, when comparing results.…”
Section: Discussionmentioning
confidence: 83%
“…Some data on dentists’ knowledge, attitudes and practices regarding HH are available in Nigeria,[ 7 ] South Africa,[ 8 ] Iran,[ 9 10 ] Jordan,[ 11 ] Brazil,[ 12 13 ] Canada,[ 14 ] Soudan,[ 15 ] United Kingdom,[ 16 17 ] Germany,[ 18 19 ] United Arab Emirates,[ 20 ] Iran[ 21 ] and United States. [ 22 ] Investigators used questionnaire,[ 7 9 10 12 18 20 22 ] direct observation[ 13 15 16 17 ] and rarely questionnaire associated with direct observation. [ 8 11 19 ] The majority of the authors concluded that there is a lack of knowledge among dentists regarding the correct agents to use and the appropriate times and sequences to HH.…”
Section: Introductionmentioning
confidence: 99%